THE INFLUENCE OF INSTRUMENTAL MUSIC ON ANXIETY LEVELS IN PATIENTS UNDERGOING HEMODIALYSIS AT JOMBANG GENERAL HOSPITAL - Asri Putri Kisfandari; Yuly Peristiowati; Indasah; Dewi Retno Puspitosari; Achmad Wahdi (Nursing Sciences Journal, 2025)
Chronic Kidney Failure (CKF) with hemodialysis is a therapy used for patients with stage 5 chronic kidney failure (ESRD) to maintain kidney function. Hemodialysis is one of the therapies for patients with chronic kidney failure followed by electrolyte fluid imbalance disorders. Where the patient's blood containing toxins is diverted to the dialyzer to filter or clean through a semi-permeable membrane and then returned to the patient's body. The purpose of this study was to provide non-pharmacological therapy to reduce anxiety in patients with hemodialysis. This study is a true experiment study with a pre and post test approach with a population of 250 and a sample of 75 people was taken using random sampling techniques. Data were collected and analyzed using the Paired T Test. The results of the study showed that the results of the Paired T test for the instrumental music group obtained a sig value (2 tailed) in the pre and post test of 0.000 <0.05, which means that there is one group that has a very significant difference. The conclusion of this study is that there is anxiety and stress in patients undergoing hemodialysis, especially in new patients. Anxiety can be minimized by diverting attention using music, including instrumental music.